2005
DOI: 10.1158/1535-7163.mct-05-0165
|View full text |Cite
|
Sign up to set email alerts
|

The rice bran constituent tricin potently inhibits cyclooxygenase enzymes and interferes with intestinal carcinogenesis in ApcMin mice

Abstract: While brown rice is a staple dietary constituent in Asia, rice consumed in the Western world is generally white, obtained from brown rice by removal of the bran. Rice bran contains the flavone tricin, which has been shown to inhibit colon cancer cell growth. We tested the hypothesis that tricin interferes with adenoma formation in the Apc Min mouse. Mice received tricin (0.2%) in their American Institute of Nutrition 93G diet throughout their postweaning life span (4 -18 weeks). Consumption of tricin reduced n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 17 publications
(14 reference statements)
2
78
0
1
Order By: Relevance
“…These methoxy groups may have somewhat hindered the interaction of the tricin molecule with glucuronyl transferase. Levels of tricin exceeded those of apigenin also in the small intestinal tract, and it remains to be seen, whether apigenin will accordingly be less efficacious than tricin in the Apc Min mouse model, in which tricin interfered significantly with small intestinal adenoma development [4]. Flavone metabolites could not be detected in the plasma or liver or gastro-intestinal tissues of mice, which had received dietary flavones, whilst preliminary inspection of the urine of mice exposed to flavones suggests the presence of three conjugate metabolites for apigenin and two for tricin (results not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These methoxy groups may have somewhat hindered the interaction of the tricin molecule with glucuronyl transferase. Levels of tricin exceeded those of apigenin also in the small intestinal tract, and it remains to be seen, whether apigenin will accordingly be less efficacious than tricin in the Apc Min mouse model, in which tricin interfered significantly with small intestinal adenoma development [4]. Flavone metabolites could not be detected in the plasma or liver or gastro-intestinal tissues of mice, which had received dietary flavones, whilst preliminary inspection of the urine of mice exposed to flavones suggests the presence of three conjugate metabolites for apigenin and two for tricin (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary administration is customarily used in rodent intervention studies. The choice of dose was based on the fact that tricin at this dose reduced adenoma multiplicity in the Apc Min mouse [4]. After 5, 6 or 7 days, mice were killed by cardiac exsanguinations under terminal anaesthesia (halothane), and blood was collected.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, tricin has in vitro antiproliferative activities on breast and colon cancer cell lines at submicromolar concentrations (Hudson et al, 2000). It effectively inhibits cyclooxygenase enzymes and interferes with murine gastrointestinal carcinogenesis (Cai et al, 2005). However, the preferred consumed form, white rice, consists exclusively of endosperm tissue, which is poor in phytochemicals.…”
mentioning
confidence: 99%
“…There are few reports on the effects of dietary tricin on intestinal carcinogenesis. Cai et al (23) reported that feeding a diet containing 0.2% tricin decreased the size and the number of intestinal adenoma formed in Apc Min/+ mice through the inhibition of cyclooxygenase (COX)-2 (23,24). Dietary tricin did not affect tumor formation in the large bowel (23).…”
mentioning
confidence: 99%